First, we will look at the left side of the equation, which is -7(a+6)+2−7(a+6)+2.
We will leave the +2+2 aside for now.
We will distribute parentheses/brackets using: x(y+z)=xy+xzx(y+z)=xy+xz
In this case, xx would represent -7−7, yy will represent aa and zz represents 66.
This means that -7(a+6)−7(a+6) is equal to -7*a+ -7*6−7⋅a+−7⋅6.
+ -+− is the same as -− so the equation would be -7*a-7*6−7⋅a−7⋅6.
7*6=427⋅6=42
The whole equation now (including the +2+2) would be 7a-42+27a−42+2.
-42+2=-40−42+2=−40 so the equation now would be -7a-40−7a−40.
Let's take a look on the right side now which is 8-3(6a+5)8−3(6a+5).
We will leave the 88 aside for now.
We will distribute parentheses/brackets again using the same thing: x(y+z)=xy+xzx(y+z)=xy+xz.
In this case, xx represents -3−3, yy represents 6a6a and zz represents 55. Don't forget that + -+− is equal to -−!
Since xx represents -3−3, yy represents so and so, the equation will be -3*6acancel(+)-3*5
-3*6a=-18a and 3*5=15.
So, -3*6a-3*5 is the same as -18a-15.
Now, we will add in the 8.
Equation:
8-18a-15
We will group like terms:
-18a+8-15 and 8-15=-7.
The equation will now be -18a-7.
There you go! You simplified both sides. Now we can solve for a.
Whole equation:
-7a-40=-18a-7. Now we add 40 to both sides.
-7a-40color(blue)+color(blue)40=-18a-7color(blue)+color(blue)40 which is the same as -7a=-18a+33.
Now we add 18a to both sides.
-7acolor(blue)+color(blue)18color(blue)a=-18a+33color(blue)+color(blue)18color(blue)a.
Now we simplify it to be 11a=33. Divide both sides by 3 and you get a=3.